Separator for electrochemical device containing organic / inorganic composite porous coating layer and electrochemical device containing the same

By using a composite pore coating of fluorine-based polymer and acrylate hybrid polymer particles and silicate particles of specific particle sizes on the separation membrane of electrochemical elements, the problem of insufficient adhesion of the separation membrane in the wet and dry state is solved, and the thermal stability and insulation performance of the battery are significantly improved.

JP2025511574AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024555997
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-03-07
Publication Date
2025-04-16
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The existing separation membranes of electrochemical elements have insufficient adhesion in both wet and dry states, resulting in easy separation of electrodes and separation membranes during use, affecting the safety and performance of the battery.

Method used

Using hybrid polymer particles containing fluorine-based polymer and acrylate polymer, as well as organic/inorganic composite pore coatings of silicate particles of specific particle sizes, combined with the porous polymer base film, the separation membrane formed can maintain structural integrity and improve adhesion under high pressure conditions.

Benefits of technology

In both wet and dry states, the adhesion between the electrode and the separation membrane can be significantly improved, the thermal stability and insulation performance of the battery can be enhanced, the risk of internal short circuits can be reduced, and the overall performance of the battery can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511574000001_ABST
    Figure 2025511574000001_ABST
Patent Text Reader

Abstract

The separator for an electrochemical device according to the present invention includes a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one side of the polymer substrate, the organic / inorganic composite porous coating layer including a particulate binder polymer and first inorganic particles, the particulate binder polymer including hybrid polymer particles of a fluorine-based polymer and an acrylic polymer and acrylic polymer particles, the acrylic polymer particles having a particle size D50(a) of 1 μm to 7 μm, the first inorganic particles having a particle size D50(b) of 200 nm to 800 nm, a / b being 2 to 15, and the hybrid polymer particles having a particle size D50 smaller than the particle size D50 of the acrylic polymer particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0064640, filed with the Korean Intellectual Property Office on May 26, 2022, the entire contents of which are incorporated herein by reference. The present invention relates to a separator for an electrochemical device having improved compression resistance and adhesive strength in a dry state (dry adhesive strength) and adhesive strength when immersed in an electrolyte (wet adhesive strength), and an electrochemical device including the same. [Background technology]

[0002] Electrochemical devices such as lithium secondary batteries are generally composed of a positive electrode / separator / negative electrode / electrolyte, and are high-energy density energy storage devices that can be charged and discharged while reversibly converting chemical energy and electrical energy, and are widely used in small electronic devices such as mobile phones and laptops. In recent years, in response to environmental issues, high crude oil prices, and energy efficiency and storage, their application to hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bicycles (e-bikes), and energy storage systems (ESSs) has rapidly expanded.

[0003] Ensuring the safety of such electrochemical devices during their manufacture and use is an important issue that must be resolved. In particular, separators made of porous polymer substrates commonly used in electrochemical devices exhibit extreme thermal shrinkage under high temperature conditions due to the characteristics of the materials and manufacturing process, and as a result, have stability problems such as internal short circuits. Recently, in order to ensure the safety of lithium secondary batteries, a separator has been developed in which a mixture of inorganic particles and a binder polymer is coated on a porous polymer substrate to form an organic / inorganic composite porous coating layer.

[0004] Typically, an electrode assembly is manufactured through a lamination process in which a separator and an electrode are bonded by heat and pressure, and the higher the heat and pressure applied in this process, the stronger the adhesion between the electrode and the separator. In recent years, the process speed has been increased to improve productivity, and as a result, the time for which heat is applied to the separator has been shortened, so the adhesive strength is ensured by increasing the pressure. However, when the organic / inorganic composite porous coating layer presses against the porous polymer substrate due to the high pressure, the thickness decreases, the pore structure is deformed, and if the inorganic particles are locally aggregated or form protrusions, the porous polymer substrate is damaged, which may ultimately lead to a deterioration in the insulation properties of the separator.

[0005] Meanwhile, when an electrode assembly is formed by stacking an electrode and a separator having an organic / inorganic composite porous coating layer, there is a high risk that the electrode and the separator will separate from each other due to insufficient interlayer adhesion, and in this case, inorganic particles that are detached during the separation process may act as local defects in the device. Therefore, a separator in which an acrylic polymer binder is applied to the organic / inorganic composite porous coating layer has been proposed to improve the adhesion between the electrode and the separator, but when an acrylic polymer binder is used, although the dry adhesion is improved, there is a problem that the wet adhesion is reduced after application to a battery due to problems such as the acrylic polymer binder swelling or dissolution by the electrolyte. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a separator for an electrochemical device that solves problems in which the insulation properties of a separator are reduced due to a high pressure applied when laminating a separator having an organic / inorganic composite porous coating layer on at least one side of a porous polymer substrate and an electrode, such as a reduction in the thickness of the porous polymer substrate or deformation of the pore structure, and at the same time, has improved adhesion to electrodes in both a dry state and a wet state.

[0007] Another object of the present invention is to provide an electrochemical device having a separator having the above-mentioned properties.

[0008] Other objects and advantages of the present invention will become apparent from the following description. Meanwhile, it will be readily apparent that the objects and advantages of the present invention can be realized by the means or methods recited in the claims, and combinations thereof. [Means for solving the problem]

[0009] A first aspect of the present invention relates to a separator for an electrochemical device, The present invention includes a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one side of the polymer substrate, The organic / inorganic composite porous coating layer includes a particulate binder polymer and a first inorganic particle, The particulate binder polymer includes hybrid polymer particles of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles, The particle size D50(a) of the acrylic polymer particles is 1 μm to 7 μm; The particle size D50(b) of the first inorganic particles is 200 nm to 800 nm; a / b is 2 to 15, The particle size D50 of the hybrid polymer particles is smaller than the particle size D50 of the acrylic polymer particles.

[0010] A second aspect of the present invention is the first aspect, wherein the particle size D50(a) of the acrylic polymer particles is 2 μm to 6 μm, the particle size D50(b) of the first inorganic particles is 300 nm to 700 nm, and a / b is 5 to 12.

[0011] A third aspect of the present invention is the first or second aspect, wherein the particle size D50 of the acrylic polymer particles is 4 to 20 times the particle size D50 of the hybrid polymer particles.

[0012] In a fourth aspect of the present invention, in any one of the first to third aspects, the hybrid polymer particles have a particle size D50 of 100 nm to 500 nm.

[0013] In a fifth aspect of the present invention, in any one of the first to fourth aspects, a mixing weight ratio of the hybrid polymer particles to the acrylic polymer particles is 8:2 to 2:8.

[0014] In a sixth aspect of the present invention, in any one of the first to fifth aspects, the Tg of the acrylic polymer contained in the hybrid polymer particles is lower by 10° C. or more than the Tg of the acrylic polymer contained in the acrylic polymer particles.

[0015] In a seventh aspect of the present invention, in the sixth aspect, the acrylic polymer contained in the hybrid polymer particles has a Tg of 10°C to 30°C, and the acrylic polymer contained in the acrylic polymer particles has a Tg of 30°C to 50°C.

[0016] In an eighth aspect of the present invention, in any one of the first to seventh aspects, the fluorine-based polymer is a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of these.

[0017] A ninth aspect of the present invention is the eighth aspect, wherein the monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3-dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride.

[0018] A tenth aspect of the present invention is the eighth aspect, wherein the fluorine-based polymer is a copolymer of vinylidene fluoride and hexafluoropropylene.

[0019] An eleventh aspect of the present invention is the eighth aspect, wherein the content of the monomer is 1% by weight to 20% by weight of the copolymer.

[0020] A twelfth aspect of the present invention is any one of the first to eleventh aspects, wherein the acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles each independently contain a repeating unit of an alkyl (meth)acrylate having an alkyl group having 1 to 18 carbon atoms.

[0021] A thirteenth aspect of the present invention is any one of the first to twelfth aspects, wherein the organic / inorganic composite porous coating layer further contains a non-particulate acrylic polymer.

[0022] In a fourteenth aspect of the present invention, in the thirteenth aspect, the non-particulate acrylic polymer has a Tg of 0° C. or lower.

[0023] A fifteenth aspect of the present invention is any one of the first to fourteenth aspects, wherein the organic / inorganic composite porous coating layer includes second inorganic particles of a different type from the first inorganic particles, and the particle size D50 of the second inorganic particles is smaller than the particle size D50 of the first inorganic particles.

[0024] In a sixteenth aspect of the present invention, in the fifteenth aspect, the second inorganic particles have a particle size D50 of 100 nm to 500 nm.

[0025] In a seventeenth aspect of the present invention, in the fifteenth aspect, the first inorganic particles are alumina, and the second inorganic particles are boehmite.

[0026] In an 18th aspect of the present invention, in any one of the 1st to 17th aspects, the organic / inorganic composite porous coating layer contains the particulate binder polymer in a range of 1 wt % to 30 wt % based on the total weight of the organic / inorganic composite porous coating layer.

[0027] A 19th aspect of the present invention is any one of the first to eighteenth aspects, wherein the organic / inorganic composite porous coating layer is formed by coating a slurry in which the particulate binder polymer and inorganic particles are dispersed in an aqueous dispersion medium onto at least one surface of the polymer substrate and drying the slurry.

[0028] A twentieth aspect of the present invention relates to an electrochemical element comprising a negative electrode, a positive electrode, and a separation membrane interposed between the negative electrode and the positive electrode, the separation membrane being related to any one of the first to nineteenth aspects.

[0029] In a twenty-first aspect of the present invention, the electrochemical device in the twentieth aspect is a lithium secondary battery. Effect of the Invention

[0030] The organic / inorganic composite porous coating layer of the separator according to the present invention includes acrylic polymer particles and first inorganic particles, the particle size D50(a) of the acrylic polymer particles is 1 μm to 7 μm, the particle size D50(b) of the first inorganic particles is 200 nm to 800 nm, and a / b is 2 to 15. Since the particle size D50 of the acrylic polymer particles is more than twice as large as the particle size D50 of the first inorganic particles, this contributes to improving the possibility that the inorganic particles of the organic / inorganic composite porous coating layer may damage the porous polymer substrate even when high pressure is applied during the lamination process with the electrodes, and to improving the phenomenon of a reduction in the thickness of the porous polymer substrate and deformation of the pore structure.

[0031] In addition, the organic / inorganic composite porous coating layer of the separator according to the present invention includes hybrid polymer particles of a fluoropolymer and an acrylic polymer having a particle size D50 smaller than that of the acrylic polymer particles. Since the fluoropolymer contained in the hybrid polymer particles is insoluble in an electrolyte, the hybrid polymer particles maintain their shape even when they are wetted with an electrolyte, even if they also contain an acrylic polymer. As a result, the separator according to the present invention maintains its adhesion to the electrode without significantly impairing its adhesion to the electrode even in a wet state. Meanwhile, the acrylic polymer particles further contribute to maintaining the adhesion of the separator to the electrode in a dry state.

[0032] Therefore, in a roll-to-roll continuous process of manufacturing an electrode assembly by stacking an electrode and the separator of the present invention, the effect of preventing the deterioration of the insulation of the separator and improving the dimensional stability and processability of the electrode assembly is obtained. In addition, when a battery is manufactured using an electrode assembly including the separator, a high binding strength can be maintained between the separator and the electrode even in a state in which the separator is soaked with an electrolyte, thereby improving the interfacial resistance characteristics. In addition, since the binder polymer particles maintain a high adhesive strength in a dry state or a wet state, the inorganic particles contained in the organic / inorganic composite porous coating layer are well fixed without being detached, thereby improving the dimensional stability of the separator. Therefore, the heat resistance safety and insulation properties of the battery are improved.

[0033] The accompanying drawings illustrate preferred embodiments of the invention and, together with the detailed description, are intended to explain the principles of the invention, and are not intended to limit the scope of the invention. Meanwhile, the shape, size, scale, ratio, etc. of elements in the drawings described in this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0034] [Figure 1] 1 is a schematic cross-sectional view of a separation membrane according to a specific embodiment of the present invention. [Diagram 2]1 is an SEM image of the surface of the separation membrane of Example 1 before being immersed in an electrolyte solution. [Diagram 3] 2 is an SEM image of a cross section of the separation membrane according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The terms or words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being consistent with the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term to best describe his / her invention. Therefore, it should be understood that the embodiments described in the present specification and the configurations shown in the drawings are merely the most preferred embodiments of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of filing this application.

[0036] FIG. 1 is a schematic cross-sectional view of a separator 10 for an electrochemical device according to one specific embodiment of the present invention.

[0037] In the present invention, the separation membrane 10 includes a porous polymer substrate 1 and an organic / inorganic composite porous coating layer 3 formed on at least one side of the polymer substrate 1. Although Fig. 1 shows that the organic / inorganic composite porous coating layer 3 is formed on both sides of the polymer substrate 1, it goes without saying that the organic / inorganic composite porous coating layer 3 may be formed on only one side of the polymer substrate 1.

[0038] The organic / inorganic composite porous coating layer 3 includes particulate binder polymers 5, 7 and first inorganic particles 9. The particulate binder polymers 5, 7 include hybrid polymer particles 5 of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles 7.

[0039] As shown in FIG. 1, the organic / inorganic composite porous coating layer 3 contains acrylic polymer particles 7 and first inorganic particles 9, the particle size D50(a) of the acrylic polymer particles 7 is 1 μm to 7 μm, the particle size D50(b) of the first inorganic particles 9 is 200 nm to 800 nm, and a / b is 2 to 15.

[0040] Since the particle size D50 of the acrylic polymer particles 7 is more than twice as large as the particle size D50 of the first inorganic particles 9, the first inorganic particles 9 of the organic / inorganic composite porous coating layer 3 contribute to improving the possibility of damaging the porous polymer substrate 1 even when high pressure is applied during the lamination process with the electrode, and the phenomenon of the thickness reduction and deformation of the pore structure of the porous polymer substrate 1. If a / b is less than 2, the compression resistance may be insufficient, and if it exceeds 15, the resistance may be excessively high. If the particle size D50(a) of the acrylic polymer particles 7 is less than 1 μm, the adhesive force may be reduced, and if it exceeds 7 μm, the resistance may be excessively high. If the particle size D50(b) of the first inorganic particles 9 is less than 200 nm, the dispersibility in the slurry may be reduced, and if it exceeds 800 nm, the thickness of the organic / inorganic composite porous coating layer may be excessively increased or excessively large pores may be formed. From this viewpoint, the particle size D50(a) of the acrylic polymer particles may be 1 μm to 6 μm, more specifically 2 μm to 6 μm, and even more specifically 3 μm to 5 μm. The particle size D50(b) of the first inorganic particles may be 300 nm to 700 nm, and even more specifically 400 nm to 600 nm. a / b may be 3 to 13, more specifically 5 to 12, and even more specifically 6 to 11.

[0041] Meanwhile, the acrylic polymer particles 7 also contribute to maintaining the adhesive strength of the separator to the electrodes in a dry state.

[0042] In addition, the organic / inorganic composite porous coating layer 3 of the separation membrane 10 according to the present invention contains hybrid polymer particles 5 of a fluoropolymer and an acrylic polymer having a particle size D50 smaller than the particle size D50 of the acrylic polymer particles 7. Since the fluoropolymer contained in the hybrid polymer particles 5 is insoluble in the electrolyte, the hybrid polymer particles 5 maintain their shape even when wet with the electrolyte, even if they also contain an acrylic polymer. As a result, the separation membrane 10 of the present invention maintains its adhesive strength with the electrode even in a wet state without significantly impairing its adhesive strength with the electrode.

[0043] Meanwhile, the particle size D50 of the hybrid polymer particles 5 is adjusted to be smaller than the particle size D50 of the acrylic polymer particles 7 to facilitate migration to the surface layer during the formation of the coating layer, so that the organic / inorganic composite porous coating layer 3 has a heterogeneity of composition morphology in the thickness direction in which the content ratio of the hybrid polymer particles 5 / acrylic polymer particles 7 present on the surface portion opposite to the surface contacting the polymer substrate 1 is larger than the content ratio of the hybrid polymer particles 5 / acrylic polymer particles 7 present inside the organic / inorganic composite porous coating layer 3, as shown in Fig. 1. This can further improve the adhesive strength of the separator 10 to the electrode when wetted with the electrolyte.

[0044] In this way, when the hybrid polymer particles 5 and / or the acrylic polymer particles 7 have the above-mentioned non-uniform composition morphology in the thickness direction, the polymer particles 5, 7 are present in greater numbers on the surface opposite to the surface in contact with the polymer substrate 1 than in the interior of the organic / inorganic composite porous coating layer 3. Therefore, the adhesive properties of the polymer particles present in greater numbers on the surface further increase the dry / wet adhesive properties to the electrode. In addition, the resistance to external stimuli such as peeling and scratching increases, improving the lamination properties to the electrode. As a result, the battery can exhibit very excellent properties in the battery assembly process such as winding and lamination. In addition, the inorganic particles, which increase in number toward the interior, improve the porosity, thereby exhibiting excellent ion conductivity properties and contributing to improved battery performance. From this viewpoint, the particle size D50 of the acrylic polymer particles 7 may be 4 to 20 times the particle size D50 of the hybrid polymer particles 5, and the particle size D50 of the hybrid polymer particles 5 may be 100 nm to 500 nm, but is not limited thereto.

[0045] Meanwhile, the mixing weight ratio of the hybrid polymer particles 5 and the acrylic polymer particles 7 may be 8:2 to 2:8, but is not limited thereto.

[0046] In the specification of the present invention, "heterogeneity of composition morphology in the thickness direction, in which the content ratio of hybrid polymer particles / acrylic polymer particles present in the surface portion of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of hybrid polymer particles / acrylic polymer particles present inside the organic / inorganic composite porous coating layer" should be interpreted as including any embodiment as long as the content ratio of hybrid polymer particles / acrylic polymer particles present in the surface portion of the organic / inorganic composite porous coating layer opposite to the surface in contact with the polymer substrate is greater than the content ratio of hybrid polymer particles / acrylic polymer particles present below (inside) the surface portion of the porous coating layer. For example, it should be construed as including all of a porous coating layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases linearly from the surface of the porous coating layer toward the polymer substrate, a porous coating layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases nonlinearly from the surface of the porous coating layer toward the polymer substrate, and a porous active layer formed such that the content ratio of hybrid polymer particles / acrylic polymer particles decreases discontinuously from the surface of the porous coating layer toward the polymer substrate.

[0047] The organic / inorganic composite porous coating layer 3 may have a heterogeneity of composition morphology in the thickness direction such that the content of the hybrid polymer particles 5 present on the surface portion opposite to the surface in contact with the polymer substrate 1 is greater than the content of the hybrid polymer particles 5 present inside the organic / inorganic composite porous coating layer 3. In addition, the organic / inorganic composite porous coating layer 3 may have a heterogeneity of composition morphology in the thickness direction such that the content of the acrylic polymer particles 7 present on the surface portion opposite to the surface in contact with the polymer substrate 1 is greater than the content of the acrylic polymer particles 7 present inside the organic / inorganic composite porous coating layer 3.

[0048] In this way, in a roll-to-roll continuous process of manufacturing an electrode assembly by stacking an electrode and the separator 10 of the present invention, the effect of improving the insulation deterioration of the separator 10 and improving the dimensional stability and processability of the electrode assembly is obtained. In addition, when a battery is manufactured using an electrode assembly including the separator 10, a high binding strength can be maintained between the separator 10 and the electrode even in a state in which the battery is immersed in an electrolyte, thereby improving the interfacial resistance characteristics. In addition, since the binder polymer particles 5 and 7 maintain a high adhesive strength in a dry state or a wet state, the inorganic particles 9 contained in the organic / inorganic composite porous coating layer 3 are well fixed without being detached, thereby improving the dimensional stability of the separator 10. As a result, the heat resistance safety and insulation properties of the battery are improved.

[0049] According to a specific embodiment of the present invention, the porous polymer substrate 1 can provide a lithium ion migration path while electrically insulating the negative and positive electrodes to prevent short circuits, and can be used without any particular limitation as long as it can be used as a separator polymer substrate for an electrochemical device. As such a polymer substrate, for example, a porous polymer film or nonwoven fabric containing one or more polymer resins such as polyolefins such as polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene can be used.

[0050] In the present invention, the thickness of the polymer substrate may be 3 μm to 50 μm. The range of the polymer substrate is not particularly limited to the above range, but if the thickness is thinner than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery. Meanwhile, the size and porosity of the pores present in the polymer substrate are also not particularly limited, but may be 0.01 μm to 50 μm and 10 vol% to 95 vol%, respectively.

[0051] The organic / inorganic composite porous coating layer 3 is formed by mixing a plurality of inorganic particles 9 and particulate binder polymers 5 and 7. The polymer substrate 1 is coated with the porous coating layer 3 including the inorganic particles 9, thereby further improving the heat resistance and mechanical properties of the separator 10. According to a preferred embodiment of the present invention, the organic / inorganic composite porous coating layer 3 is disposed on both sides of the polymer substrate 1. As such, the porous coating layer 3 is formed on both sides of the polymer substrate 1, thereby improving the wet adhesive strength and dry adhesive strength between the positive electrode and the separator and between the negative electrode and the separator.

[0052] The organic / inorganic composite porous coating layer 3 may have a microporous structure due to an interstitial volume between the inorganic particles 9 and the particulate binder polymers 5 and 7. The inorganic particles 9 also serve as a kind of spacer capable of maintaining the physical form of the porous coating layer 3. The interstitial volume means a space defined by the inorganic particles 9 and the particulate binder polymers 5 and 7 substantially coming into contact with each other. In addition, the inorganic particles 9 generally have a property that their physical properties do not change even at high temperatures of 200° C. or more, so that the separator 10 has excellent heat resistance due to the organic / inorganic composite porous coating layer 3. In the present invention, the organic / inorganic composite porous coating layer 3 may have a thickness of 1 μm to 50 μm, 2 μm to 30 μm, or 2 μm to 20 μm based on the thickness formed on one surface of the polymer substrate 1.

[0053] In the present invention, the particulate polymers 5 and 7 refer to binder polymers that are added in particulate form to the dispersion medium during the formation of the porous coating layer 3 and maintain the added particulate form after coating and drying, and are distinguished from "non-particulate" binder polymers that are defined as those that dissolve in the solvent or, even if not dissolved in the solvent, lose their particulate form during the drying process during the formation of the coating layer and transform into a film-like form. That is, in the present invention, "particles" are defined as those that maintain substantially the same particle form as added, and the form is usually, but not limited to, circular particles. In this way, the polymer particles maintain their particulate form, which contributes to improving the phenomenon that the pores of the polymer substrate are blocked by hardly penetrating into the pores of the porous polymer substrate.

[0054] In one embodiment of the present invention, the particulate binder polymers 5 and 7 may account for 90% by weight or more or 99% by weight or more of the binder components present in the porous coating layer 3. In this specification, the particulate binder polymers 5 and 7 may be called polymer particles, resin particles, binder particles, or the like. The particulate binder polymers 5 and 7 form the porous coating layer 3 having a layered structure by bonding the inorganic particles 9 to each other and bonding the inorganic particles 9 to the polymer substrate 1.

[0055] The hybrid polymer particles 5 can be produced, for example, by reference to WO2020 / 263936, which is incorporated by reference into the present invention.

[0056] The fluorine-based polymer contained in the hybrid polymer particles is insoluble in the electrolyte and may be a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of these.

[0057] Examples of the vinylidene fluoride and other polymerizable monomers include, but are not limited to, one or more selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3-dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride. In particular, the fluorine-based polymer may be a copolymer of vinylidene fluoride and hexafluoropropylene. The content of vinylidene fluoride and other polymerizable monomers may be, but is not limited to, 1% by weight to 20% by weight of the copolymer.

[0058] In the present invention, the content of the comonomer in the PVDF-based polymer can be measured by 1H-NMR using Varian 500MHz. For details of the measurement method, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. For checking the NMR spectrum, a suitable device such as Bruker Avance III HD700Mhz NMR or Varian 500MHz NMR can be used.

[0059] The acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles may each independently contain a repeating unit of an alkyl (meth)acrylate having an alkyl group having 1 to 18 carbon atoms, but is not limited thereto.

[0060] In one embodiment of the present invention, the Tg of the acrylic polymer contained in the hybrid polymer particles may be lower than the Tg of the acrylic polymer contained in the acrylic polymer particles by 10° C. or more. Since the lower the Tg of the acrylic polymer, the more advantageous it is for improving the adhesive strength, the dry / wet adhesive strength of the hybrid polymer particles to the electrodes can be further improved by selecting an acrylic polymer having a low Tg for the hybrid polymer particles.

[0061] More specifically, the Tg of the acrylic polymer contained in the hybrid polymer particles may be 10° C. to 30° C., and the Tg of the acrylic polymer contained in the acrylic polymer particles may be 30° C. to 50° C. Even if the acrylic polymer contained in the hybrid polymer particles has a low Tg, it can maintain a particulate shape even at room temperature due to the hybrid fluorine-based polymer. In addition, when the acrylic polymer contained in the acrylic polymer particles is selected to have a Tg of room temperature or higher, it can maintain a particulate shape at room temperature and exhibit electrode adhesive strength when laminated with an electrode.

[0062] The acrylic polymer may have a glass transition temperature (Tg) of 40° C. or less.

[0063] More specifically, the acrylic polymer may be a polymer containing a carboxylate ester as a repeating unit, and may preferably be a (meth)acrylic ester. Specific examples of such (meth)acrylic esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. Examples of the acrylate include decyl acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate, and may be one or more selected from these. Among these, it is preferably one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, and particularly preferably methyl (meth)acrylate.

[0064] The organic / inorganic composite porous coating layer may include the particulate binder polymer in an amount ranging from 1% by weight to 30% by weight of the organic / inorganic composite porous coating layer, but is not limited thereto.

[0065] The organic / inorganic composite porous coating layer may further include a non-particulate acrylic polymer. The non-particulate acrylic polymer is an acrylic polymer that is not dissolved in an aqueous dispersion medium but cannot maintain a particulate state, for example, an acrylic polymer with a low Tg of 0°C or less. Such a non-particulate acrylic polymer can improve the adhesive strength of the organic / inorganic composite porous coating layer to the electrode, the binding strength between inorganic particles, and between the inorganic particles and the polymer substrate. The non-particulate acrylic polymer may be added in an amount of 10 wt% or less based on the total weight of the binder polymer contained in the organic / inorganic composite porous coating layer, but is not limited thereto.

[0066] Meanwhile, the first inorganic particles contained in the organic / inorganic composite porous coating layer are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles are not particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the applied electrochemical device (e.g., 0V to 5V based on Li / Li+). In particular, when the first inorganic particles having ion transfer ability are used, the ion conductivity in the electrochemical device can be increased to improve performance. In addition, when inorganic particles having a high dielectric constant are used as the first inorganic particles, they can contribute to increasing the dissociation degree of the electrolyte salt, for example, lithium salt, in the liquid electrolyte, thereby improving the ion conductivity of the electrolyte solution.

[0067] For the reasons described above, the first inorganic particles may include high dielectric constant inorganic particles having a dielectric constant of 5 or more, or 10 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0 <x<1、0<y<1である)、Pb(Mg 1 / 3 Nb 2 / 3)O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, alumina (Al2O3), boehmite, SiC, TiO2, etc. can be used alone or in combination of two or more. Further, when the above-mentioned high dielectric constant inorganic particles and inorganic particles having lithium ion transfer ability are used in combination, these synergistic effects can be doubled.

[0068] Non-limiting examples of the inorganic particles having lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5, etc. of (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4, etc. of lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass such as Li3PO4 - Li2S - SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glass such as LiI - Li2S - P2S5 (Li x P y S z, such as 0 < x < 3, 0 < y < 3, 0 < z < 7, or a mixture thereof.

[0069] On the other hand, the organic / inorganic composite porous coating layer may have a particle size D50 smaller than that of the first inorganic particles and may further contain second inorganic particles of a type different from the first inorganic particles. By mixing such second inorganic particles, the packing density of the porous coating layer can be improved, and heat resistance and the like can be further improved. From this perspective, the particle size D50 of the second inorganic particles can be 100 nm to 500 nm.

[0070] As the second inorganic particles, the types of the aforementioned first inorganic particles and the like can be used. In particular, alumina can be used as the first inorganic particles, and boehmite can be used as the second inorganic particles.

[0071] In the organic / inorganic composite porous coating layer, the content ratio of the inorganic particles is determined in consideration of the thickness, pore size, and porosity of the finally produced organic / inorganic composite porous coating layer. Based on the weight ratio, the inorganic particles can be contained in the range of 70% to 99% by weight with respect to 100% by weight of the porous coating layer. If the content of the inorganic particles is less than 70% by weight, the heat resistance may decrease. On the other hand, if the content of the inorganic particles is too high, the amount of the binder is too small, and the adhesion of the porous coating layer may decrease.

[0072] On the other hand, in one embodiment of the present invention, the separation membrane including the organic / inorganic composite porous coating layer can be manufactured by mixing binder particles and inorganic particles with an aqueous dispersion medium to produce a slurry for forming the coating layer, and then coating the slurry on at least one side surface of the polymer substrate.

[0073] As the coating method, dip coating, die coating, roll coating, comma coating, or a mixed method thereof can be used.

[0074] In one embodiment of the present invention, the aqueous dispersion medium may include one or more of water and alcohol having 1 to 5 carbon atoms. For example, the aqueous dispersion medium may include a mixture of water and isopropyl alcohol. By using an aqueous dispersion medium in the preparation method, the binder particles are not dissolved in the dispersion medium and are dispersed in the aqueous dispersion medium while maintaining their particle shape. For this reason, the binder particles can maintain a particle state in the prepared organic / inorganic composite porous coating layer and do not flow into the pores of the polymer substrate.

[0075] Meanwhile, in one embodiment of the present invention, the slurry for forming the coating layer is preferably controlled so that the solid content concentration excluding the dispersion medium is in the range of 20wt% to 50wt%. It is advantageous to obtain a separator having an organic / inorganic composite porous coating layer having non-uniform composition morphology according to the present invention by controlling the solid content concentration, the average particle size and the content ratio of the binder particles to be added within the above-mentioned ranges.

[0076] Meanwhile, in the present invention, the separator may be applied to an electrochemical device. The electrochemical device may include an anode and a cathode, and the separator may be interposed between the anode and the cathode. The electrochemical device may include any device that performs an electrochemical reaction, and specific examples thereof include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors. In particular, among the secondary batteries, lithium ion secondary batteries, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries, are preferred.

[0077] In a specific embodiment of the present invention, the electrochemical device can be manufactured according to a conventional method known in the art. According to an embodiment of the present invention, the electrochemical device can be constructed by interposing the above-mentioned separator between the positive electrode and the negative electrode.

[0078] That is, the separator prepared by the above-mentioned method is interposed between the negative electrode and the positive electrode, and is manufactured into an electrode assembly by a lamination process in which heat and / or pressure are applied to bond them. In one embodiment of the present invention, the lamination process can be performed by a roll press device including a pair of pressure rollers. That is, the negative electrode, the separator, and the positive electrode can be sequentially stacked and then inserted between the pressure rollers to achieve interlayer bonding. At this time, the lamination process can be performed by a hot pressing method.

[0079] The electrode assembly, in which the negative electrode, the separator, and the positive electrode are stacked, is inserted into a battery case, and then an electrolyte is injected into the battery case, thereby completing the manufacture of the electrochemical device.

[0080] In one embodiment of the present invention, the electrode is not particularly limited, and the electrode active material may be prepared in a form in which it is attached to the electrode current collector according to a conventional method known in the art. Among the electrode active materials, non-limiting examples of the positive electrode active material include conventional positive electrode active materials that can be used in the positive electrode of conventional electrochemical devices, and in particular, lithium intercalation materials such as lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a composite oxide formed by a combination thereof are preferred. Non-limiting examples of the negative electrode active material include conventional negative electrode active materials that can be used in the negative electrode of conventional electrochemical devices, and in particular, lithium intercalation materials such as lithium metal or lithium alloy, carbon, petroleum coke, activated carbon, graphite, or other carbons are preferred. Non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.

[0081] The electrolyte that can be used in the present invention is A+ B - A salt having the structure: + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.

[0082] The electrolyte injection can be performed at an appropriate stage during the battery manufacturing process depending on the manufacturing process and required properties of the final product. That is, it can be applied before the battery assembly or at the final stage of the battery assembly. In addition to the general winding process, lamination (stack) and folding processes of the separator and the electrode are possible processes for applying the electrode assembly of the present invention to a battery.

[0083] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various different forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0084] [Example 1] 8.2 parts by weight of hybrid polymer particles [Arkema, LBG4330LX, D50: 300 nm, hybrid polymer particles in which a copolymer of VDF and HFP polymerized at a molar ratio of 95: 5 and a copolymer of ethyl acrylate and methyl methacrylate (Tg 20°C) are mixed at a weight ratio of 7: 3], 8.2 parts by weight of acrylic polymer particles [D50: 5 μm, a copolymer of styrene and butyl acrylate (Tg 40°C)], and 80 parts by weight of inorganic particles (Al2O3, D50: 500 nm) were added and dispersed in water to prepare a dispersion liquid (solid concentration 35% by weight) for forming a porous coating layer.

[0085] Next, a polyethylene polymer substrate (porosity 40%, thickness 9μm) was prepared, and the dispersion was applied to both sides of the surface of the polymer substrate by a bar coating method using a doctor blade, and then dried with hot air at 50℃ using a heat gun to form a porous coating layer with a thickness of 12μm on one side. The particle size D50 of the acrylic polymer particles / particle size D50(a / b) of the first inorganic particles Al2O3 was 10.

[0086] FIG. 2 is an SEM image of the surface of the separation membrane of Example 1 before it is immersed in the electrolyte, and FIG. 3 is an SEM image of a cross section of the separation membrane according to Example 1.

[0087] [Example 2] A porous coating layer was formed in the same manner as in Example 1, except that the content of the hybrid polymer particles was changed to 10.2 parts by weight, the content of the acrylic polymer particles was changed to 10.2 parts by weight, and the content of the inorganic particles was changed to 75 parts by weight to prepare a dispersion for forming a porous coating layer (solid concentration 35% by weight). The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles, Al2O3, was 10.

[0088] [Example 3] A porous coating layer was formed in the same manner as in Example 1, except that 0.9 parts by weight of non-particulate acrylic polymer (Toyochem, CSB130, particle size 150 nm, Tg-30°C) based on the solid content was further added to the water. The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 10.

[0089] [Example 4] A porous coating layer was formed in the same manner as in Example 1, except that a total of 80 parts by weight of inorganic particles (Al2O3, D50:500nm) and boehmite (D50:300nm) were added in a weight ratio of 85:15 instead of 80 parts by weight of inorganic particles (Al2O3, D50:500nm). The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 10.

[0090] [Comparative Example 1] A porous coating layer was formed in the same manner as in Example 1, except that the hybrid polymer particles were not added, and the content of the acrylic polymer particles was changed to 16.4 parts by weight to prepare a dispersion for forming a porous coating layer (solid concentration 35% by weight). The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 10.

[0091] [Comparative Example 2] A porous coating layer was formed in the same manner as in Example 1, except that the content of the hybrid polymer particles was changed to 16.4 parts by weight without adding the acrylic polymer particles, and the dispersion for forming the porous coating layer (solid concentration 35%) was prepared. The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 0.

[0092] [Comparative Example 3] A porous coating layer was formed in the same manner as in Example 1, except that 8.2 parts by weight of acrylic polymer particles having a small particle size D50 [D50: 0.9 μm styrene and butyl acrylate copolymer (Tg 40° C.)] was added instead of 8.2 parts by weight of acrylic polymer particles having a D50 of 5 μm in Example 1. The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 1.8.

[0093] [Comparative Example 4] A porous coating layer was formed in the same manner as in Example 1, except that 8.2 parts by weight of acrylic polymer particles having a small particle size D50 [D50: 0.4 μm styrene and butyl acrylate copolymer (Tg 40° C.)] was added instead of 8.2 parts by weight of acrylic polymer particles having a D50 of 5 μm in Example 1. The particle size D50 of the acrylic polymer particles / particle size D50 (a / b) of the first inorganic particles Al2O3 was 0.8.

[0094] Measurement of average particle size D50 D50 can be defined as the particle size at 50% of the particle size distribution, and was measured using the laser diffraction method.

[0095] Measurement of Tg Using DSC, Tg of a 25 mg sample was measured under conditions of a nitrogen atmosphere, room temperature to 300°C, and a heating rate of 10°C / min.

[0096] Preparation of wet adhesion test specimens The separator and the positive electrode obtained in each Example and Comparative Example were laminated, impregnated with 1.0 g of the electrolyte (ethylene carbonate: ethyl methyl carbonate = 7: 3, content ratio, LiPF61M), and left at room temperature for 24 hours. Then, the laminate was made using a hot press to prepare a test piece. At this time, the pressure was applied at 70 ° C and 5 kgf for 5 minutes. The size of the test piece was 2 cm × 6 cm.

[0097] The positive electrode was prepared as follows: LiNi 0.8 Co 0.1 Mn 0.1 O2, PVDF and carbon black were mixed in a weight ratio of 97.0:1.5:1.5 and dispersed in 2-methyl-2-pyrrolidone to prepare a positive electrode slurry, which was then coated on an aluminum current collector, dried and rolled to prepare a positive electrode.

[0098] Preparation of dry adhesion test specimens The separator and the negative electrode obtained in each Example and Comparative Example were stacked and laminated using a hot press to prepare a test piece. At this time, pressure was applied at 60° C. and 6.5 MPa for 1 second. The size of the test piece was 2.5 cm × 6 cm.

[0099] The negative electrode was prepared as follows: Graphite, SBR, and CMC were mixed in a weight ratio of 89.2:10:0.8, and dispersed in distilled water to prepare a negative electrode slurry, which was then coated onto a copper current collector, dried, and rolled to prepare a negative electrode.

[0100] Measurement of adhesion to electrodes The wet adhesion and dry adhesion of the separator were evaluated using each test piece prepared as above, and the results are summarized in Table 1 below. Each test piece was prepared and left at room temperature for 1 hour, and then the adhesion was measured. The adhesion was measured using a tensile tester (UTM device) by peeling at an angle of 180° for dry adhesion and 90° for wet adhesion.

[0101] [Table 1]

[0102] As can be seen from Table 1, Comparative Example 1 has high dry adhesion but low wet adhesion, which may cause a decrease in battery performance when applied to an actual battery. Comparative Example 2 has low dry adhesion, which may cause a decrease in adhesion during the manufacturing process of the electrode assembly. Comparative Examples 3 and 4 have low compression resistance, which may cause the thickness of the porous polymer substrate to decrease and the pore structure to deform due to the high pressure applied when laminating the separator and the electrode, which may cause a decrease in the insulation properties of the separator. On the other hand, the separators according to the examples have good levels of both wet and dry adhesion, which may provide excellent electrochemical effects during the manufacturing process of the electrode assembly and during battery operation. [Explanation of symbols]

[0103] 1: Polymer base material 3: Organic / inorganic composite porous coating layer 5: Hybrid polymer particles 7: Acrylic polymer particles 9: Inorganic particles 10: Separation membrane

Claims

1. The present invention includes a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one side of the polymer substrate, The organic / inorganic composite porous coating layer includes a particulate binder polymer and a first inorganic particle, The particulate binder polymer includes hybrid polymer particles of a fluorine-based polymer and an acrylic polymer, and acrylic polymer particles, The particle size D50(a) of the acrylic polymer particles is 1 μm to 7 μm; The particle size D50(b) of the first inorganic particles is 200 nm to 800 nm; a / b is 2 to 15; A separator for an electrochemical device, wherein a particle size D50 of the hybrid polymer particles is smaller than a particle size D50 of the acrylic polymer particles.

2. 2. The separator for electrochemical devices according to claim 1, wherein the acrylic polymer particles have a particle size D50(a) of 2 μm to 6 μm, the first inorganic particles have a particle size D50(b) of 300 nm to 700 nm, and a / b is 5 to 12.

3. 2. The separator for an electrochemical device according to claim 1, wherein the particle size D50 of the acrylic polymer particles is 4 to 20 times the particle size D50 of the hybrid polymer particles.

4. 2. The separator for an electrochemical device according to claim 1, wherein the hybrid polymer particles have a particle size D50 of 100 nm to 500 nm.

5. 2. The separator for electrochemical devices according to claim 1, wherein a mixing weight ratio of the hybrid polymer particles to the acrylic polymer particles is 8:2 to 2:

8.

6. 2. The separator for an electrochemical device according to claim 1, wherein the Tg of the acrylic polymer contained in the hybrid polymer particles is at least 10° C. lower than the Tg of the acrylic polymer contained in the acrylic polymer particles.

7. The acrylic polymer contained in the hybrid polymer particles has a Tg of 10° C. to 30° C., and the acrylic polymer contained in the acrylic polymer particles has a Tg of 30° C. to 50° C. The separator for an electrochemical device according to claim 6.

8. 2. The separator for an electrochemical device according to claim 1, wherein the fluoropolymer is a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more of them.

9. 9. The separator for electrochemical devices according to claim 8, wherein the monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3-dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride.

10. 9. The separator for an electrochemical device according to claim 8, wherein the fluorine-based polymer is a copolymer of vinylidene fluoride and hexafluoropropylene.

11. 9. The separator for electrochemical devices according to claim 8, wherein the content of the monomer is 1% by weight to 20% by weight of the copolymer.

12. 2. The separator for electrochemical elements according to claim 1, wherein the acrylic polymer constituting the hybrid polymer particles and the acrylic polymer constituting the acrylic polymer particles each independently contain a repeating unit of an alkyl (meth)acrylate having an alkyl group having 1 to 18 carbon atoms.

13. The separator for an electrochemical device according to claim 1 , wherein the organic / inorganic composite porous coating layer further comprises a non-particulate acrylic polymer.

14. The separator for an electrochemical device according to claim 13 , wherein the non-particulate acrylic polymer has a Tg of 0° C. or lower.

15. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer comprises second inorganic particles different from the first inorganic particles, and the particle size D50 of the second inorganic particles is smaller than the particle size D50 of the first inorganic particles.

16. The separator for an electrochemical device according to claim 15, wherein the second inorganic particles have a particle size D50 of 100 nm to 500 nm.

17. The separator for an electrochemical device according to claim 15 , wherein the first inorganic particles are alumina and the second inorganic particles are boehmite.

18. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer comprises the particulate binder polymer in a range of 1 wt % to 30 wt % based on a total weight of the organic / inorganic composite porous coating layer.

19. 2. The separator for electrochemical devices according to claim 1, wherein the organic / inorganic composite porous coating layer is formed by coating a slurry in which the particulate binder polymer and inorganic particles are dispersed in an aqueous dispersion medium on at least one surface of the polymer substrate, and drying the slurry.

20. An electrochemical element comprising a negative electrode, a positive electrode, and a separator interposed between the negative electrode and the positive electrode, An electrochemical element, wherein the separation membrane is the separation membrane according to any one of claims 1 to 19.

21. 21. The electrochemical device according to claim 20, wherein the electrochemical device is a lithium secondary battery.

Citation Information

Patent Citations

  • Fluoropolymer resins containing ionic or ionizable groups and products containing same

    JP2003523419A

  • Lithium-ion battery separator

    JP2021501453A

  • Separator for lithium secondary battery and a method of making the same

    KR1020160118979A

  • Lubrication control device and control method of machine tool lubrication member

    KR1020230027549A

  • The advertisement targeting system for personalized medical institutions using virtual reality-based user group data

    KR1020230114866A